2021
DOI: 10.2147/ijgm.s312465
|View full text |Cite|
|
Sign up to set email alerts
|

Anxiety Levels Amid the COVID-19 Lockdown in Saudi Arabia

Abstract: Objective To assess the prevalence of anxiety and factors associated with it during the peak of the outbreak in Saudi Arabia. Materials and Methods This cross-sectional research screened the general public using the Generalized Anxiety Disorder Scale-7 to detect anxiety levels. The questionnaire was distributed online during May 2020, while lockdowns were enforced. A total of 3017 respondents from all five main regions of Saudi Arabia completed the survey. The prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 12 publications
3
35
0
Order By: Relevance
“…Geographical locations that were identified as COVID-19 epicentres had higher instances of anxiety compared to non-epicentre areas [ 27 , 28 , 35 , 42 , 72 , 81 , 110 ]. Moreover, COVID-19 prevalent areas that exemplified elevated testing rates reported decreased anxiety [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Geographical locations that were identified as COVID-19 epicentres had higher instances of anxiety compared to non-epicentre areas [ 27 , 28 , 35 , 42 , 72 , 81 , 110 ]. Moreover, COVID-19 prevalent areas that exemplified elevated testing rates reported decreased anxiety [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…For measuring the included adverse psychological outcomes, a total of nine tools were used. Both Depression Anxiety Stress Scales (DASS-21) (Alamri et al, 2020;Alghamdi et al, 2021;AlHadi et al, 2021;Alkhamees et al, 2020;Zakout et al, 2020) and General Anxiety Disorder-7 (GAD-7) were used in a total of five studies each (Albagmi et al, 2021;Alqahtani et al, 2021;Alsaif et al, 2021;Alyami et al, 2021;BinDhim et al, 2021), and Patient Health Questionnaire-9 (PHQ-9) in three studies (AlHusseini et al, 2021;Alyami et al, 2021;BinDhim et al, 2021). In addition, other scales such as Center for Epidemiological Studies-Depression (CES-D) (Sonbol et al, 2021), Impact Of Events Scale-Revised (IES-R) (Alkhamees et al, 2020), Perceived Stress Scale-10 (PSS-10) (Hawash et al, 2021), Beck Depression Inventory (BDI) (Alotaibi & Boukelia, 2021), and Post-traumatic Stress Disorder Checklist-Specific (PCLS) (Alshehri et al, 2020) were used in the included studies.…”
Section: Measurements Used In the Included Studiesmentioning
confidence: 99%
“…Although five studies reported younger age groups being at a higher risk of mental health problems (Alamri et al, 2020;Albagmi et al, 2021;AlHadi et al, 2021;Alkhamees et al, 2020;Alqahtani et al, 2021), elderly people were reported in two studies (Alyami et al, 2021;Sonbol et al, 2021). In respect to marital status, single or unmarried participants were more likely to suffer from mental disorders, as reported in six studies (Alamri et al, 2020;Albagmi et al, 2021;AlHusseini et al, 2021;Alshehri et al, 2020;Hawash et al, 2021;Sonbol et al, 2021) and divorced in one study (Alyami et al, 2021). Similarly, education level (lower), residence, income (lower), and nationality (non-Saudi) were found to be associated with mental health problems.…”
Section: Sociodemographic Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall score range on the GAD-7 scale is 0 to 21, with 5–9 indicating mild anxiety symptoms, 10–14 indicating moderate anxiety symptoms, and 15 indicating severe anxiety symptoms. The reliability of GAD-7 in screening anxiety is reported in the Arabic language as highly consistent and with Cronbach α = 0.89 [ 37 ].…”
Section: Methodsmentioning
confidence: 96%